Hard carbon material and preparation method thereof, negative plate and battery
By setting core-shell structure, doping oxygen anions and decreasing heteroatom concentration in hard carbon materials, the problems of reversible specific capacity and first-time Coulomb efficiency of hard carbon materials in battery applications are solved, and the efficient cycling performance of the battery is achieved.
Patent Information
- Application Number
- CN202411998235.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
Hard carbon materials have problems with reversible specific capacity and low first-time Coulomb efficiency in battery applications.
By setting a unique core-shell structure and an appropriate specific surface area, the carbon core is doped with oxygen anions and decreasing the heteroatom concentration from the center of the carbon core to the direction of the carbon shell, a hard carbon material with excellent electrochemical properties is prepared.
It significantly improves the reversible specific capacity of the battery and the first-time Coulomb efficiency, and improves the cycling performance of the battery.
Smart Images

Figure CN119812267A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a hard carbon material and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] With the rapid development of the new energy vehicle industry, the demand for lithium batteries has also increased, but the global lithium resource reserves are limited and unevenly distributed. Therefore, the development of new alternative energy storage devices with high performance and low price has attracted much attention. Since sodium and lithium have similar physical and chemical properties; sodium ion batteries work in a similar way to lithium ion batteries and have abundant resource reserves, they are considered to be a potential substitute for lithium ion batteries.
[0003] The research on negative electrode materials for sodium-ion batteries is the key to improving their performance. Among the negative electrode materials discovered so far, hard carbon negative electrode materials have received extensive attention due to their advantages such as low sodium embedding platform, high theoretical capacity, good cycle performance, and simple processing. Although hard carbon materials have many advantages mentioned above, the practical application of hard carbon still faces some challenges, especially the low reversible specific capacity and first coulombic efficiency. Summary of the invention
[0004] The present invention provides a hard carbon material, which can significantly improve the reversible specific capacity and the first coulombic efficiency of a battery by arranging a unique core-shell structure and a suitable specific surface area.
[0005] The present invention also provides a method for preparing the hard carbon material. The method can prepare the hard carbon material and is simple to operate.
[0006] The present invention also provides a negative electrode sheet comprising the hard carbon material, which is beneficial to ensuring the overall reversible specific capacity and first coulombic efficiency of the battery.
[0007] The present invention also provides a battery comprising the negative electrode sheet, and the battery has excellent cycle performance.
[0008] In detail, in a first aspect, the present invention provides a hard carbon material, comprising a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, the carbon core is doped with oxygen anions, the oxygen anions contain heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell, and the specific surface area of the hard carbon material is B, and B satisfies 5m 2 / g≤B≤15m 2 / g.
[0009] Furthermore, in the hard carbon material, the doping amount of oxygen anions is 1-5wt%.
[0010] Furthermore, the heteroatom includes at least one of N, P, and S.
[0011] Furthermore, the hard carbon material satisfies the following formula 1 and / or formula 2:
[0012] 27%≤V cp / V p ×100%≤36% Formula 1,
[0013] 0.1%≤F≤0.5% Formula 2,
[0014] Among them, V cp is the closed pore volume of the hard carbon material, in cm 3 / g,V p is the pore volume of the hard carbon material, in cm 3 / g, F is the ash content of the hard carbon material.
[0015] Furthermore, the hard carbon material satisfies the following formula 3 and formula 4:
[0016] V cp ×d 002 ×10 -7 =a Formula 3,
[0017] 0.5×10 -8 cm 4 / g≤a≤0.2×10 -7 cm 4 / g Formula 4,
[0018] Among them, V cp is the closed pore volume of the hard carbon material, in cm 3 / g,d 002 is the carbon interlayer spacing of hard carbon materials, in nm.
[0019] Furthermore, 0.375nm≤d 002 ≤0.395nm.
[0020] Further, the graphitization degree of the carbon core is greater than the graphitization degree of the hard carbon material;
[0021] Preferably, the hard carbon material satisfies: the lattice constant of the a-axis of the graphite crystal is 2-6 nm, and the lattice constant of the c-axis of the graphite crystal is 1-1.5 nm;
[0022] The carbon core satisfies: the lattice constant of the a-axis of the graphite crystal is 3-8nm, and the lattice constant of the c-axis of the graphite crystal is 1.5-2nm.
[0023] In a second aspect, the present invention provides a method for preparing the hard carbon material as described in the first aspect, comprising the following steps:
[0024] The carbon source and the heteroatom doping source are mixed and carbonized at 150-600° C. in a protective atmosphere for 0.5-6 h to obtain a precursor I;
[0025] The precursor I is subjected to secondary carbonization treatment at 900-1600° C. in a protective atmosphere for 1-10 hours to obtain the precursor II;
[0026] After the precursor II and the coating agent are mixed, the temperature is raised to 300-600°C at a heating rate of 1-5°C / min in a protective atmosphere, and the temperature is kept for 2-12 hours. The temperature is then raised to 800-1300°C at a heating rate of 1-10°C / min, and the temperature is kept for 1-10 hours to obtain the hard carbon material.
[0027] Furthermore, the carbon source is a lignin material and / or a cellulose material;
[0028] Preferably, the carbon source is mixed after being pretreated; the pretreatment includes the following process:
[0029] The lignin and / or cellulose materials are pre-carbonized at 300-800° C. in a protective atmosphere, and the solid product obtained by the pre-carbonization is acid-washed to obtain the pre-treated carbon source.
[0030] Furthermore, the mass ratio of the heteroatom doping source to the carbon source is 1-5wt%;
[0031] Preferably, the heteroatom doping source includes at least one of urea, ammonium persulfate, melamine, ammonium polyphosphate, and sodium dodecyl sulfate;
[0032] Preferably, the coating agent includes at least one of asphalt, phenolic resin, beta resin, glucose and citric acid.
[0033] In a third aspect, the present invention provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer coated on at least one surface of the current collector, wherein the negative electrode active material layer comprises the hard carbon material described in the first aspect or the hard carbon material prepared by the preparation method described in the second aspect.
[0034] In a fourth aspect, the present invention provides a battery, comprising a positive electrode sheet and the negative electrode sheet described in the third aspect.
[0035] The hard carbon material provided by the present invention can significantly improve the reversible specific capacity and first coulombic efficiency of the assembled battery by arranging a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, and further limiting the carbon core to include heteroatoms decreasing in the direction from the center of the carbon core to the carbon shell, as well as the range of the specific surface area of the hard carbon material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0037] Figure 1 A schematic diagram of the structure of a hard carbon material according to a specific embodiment of the present invention;
[0038] In the figure, 01-carbon core, 02-carbon shell;
[0039] Figure 2 is a Raman image of the hard carbon material of Example 1 of the present invention;
[0040] Figure 3 is a SEM image of the hard carbon material of Example 1 of the present invention;
[0041] Figure 4 is the XRD pattern of the hard carbon material of Example 1 of the present invention;
[0042] Figure 5 This is the first week GCD curve of the hard carbon material of Example 1 of the present invention;
[0043] Figure 6 This is a Raman image of the hard carbon material of Comparative Example 2 of the present invention;
[0044] Figure 7 This is a SEM image of the hard carbon material of Comparative Example 2 of the present invention;
[0045] Figure 8 This is the XRD pattern of the hard carbon material of Comparative Example 2 of the present invention;
[0046] Fig. 9 This is the first week GCD curve of the hard carbon material of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] In a first aspect, the present invention provides a hard carbon material, see Figure 1 The hard carbon material comprises a carbon core and a carbon shell 02 located on at least a portion of the surface of the carbon core 01, wherein the carbon core is doped with oxygen anions (AOy x- , x is any natural number from 1 to 3, y is any natural number from 1 to 4), the oxygen anion comprises a heteroatom (A), and the concentration of the heteroatom decreases from the center of the carbon core to the direction close to the carbon shell, and the specific surface area of the hard carbon material is B, and B satisfies 5m 2 / g≤B≤15m 2 / g.
[0049] The hard carbon material of the present invention can effectively improve the reversible specific capacity and the first coulombic efficiency of the battery. The main reasons include: the carbon core 01 is doped with oxygen anions. On the one hand, since heteroatoms and carbon atoms can form a bond to form CAC (see Figure 1 ), the bond length of the traditional CC bond changes, making the carbon core more conducive to sodium ion transmission. On the other hand, after the heteroatoms form bonds with carbon atoms, the change in electron cloud density can further improve the electronic conductivity of the hard carbon material, improve the kinetics, and thus improve the sodium ion storage performance of the hard carbon material; and the concentration of heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell, which can make the overall hard carbon material form a unique structure with a gradient change in conductivity and a gradient change in lithium / sodium ion storage site, thereby improving the reversible specific capacity and the first coulombic efficiency of the battery containing the hard carbon material. In addition, the carbon shell 02 is located on the outer surface of the carbon core 01, which can protect the doping structure of the carbon core, thereby further reducing the irreversible capacity loss in the sodium ion transmission process. The specific surface area of the hard carbon material is within the above range, which enables the hard carbon material to have more active sites that can be used for the embedding and de-embedding of lithium / sodium ions. The hard carbon material with this specific surface area can improve the reversible specific capacity of the negative electrode material, thereby improving the first coulombic efficiency of the battery.
[0050] In a specific embodiment, in the hard carbon material, the doping amount of oxygen anions is 1-5 wt %.
[0051] Among them, the above-mentioned doping amount can further improve the conductivity and sodium ion storage performance of the hard carbon material under the premise of ensuring the integrity of the carbon network of the hard carbon material. The present invention also found that within the above-mentioned doping range, the doping amount of oxygen anions is positively correlated with the carbon layer spacing of the hard carbon material, that is, the higher the doping amount of oxygen anions, the larger the carbon layer spacing of the hard carbon material.
[0052] In a specific embodiment, the heteroatom includes at least one of N, P, and S.
[0053] Among them, the types of heteroatoms have great differences in their effects on the structure of hard carbon materials. The introduction of N elements can better improve the conductivity of hard carbon materials. The introduction of P elements has a significant effect on the enrichment of graphite crystallites and pore structures of hard carbon materials. The introduction of S elements can enhance the electrochemical activity of hard carbon materials and the adsorption performance of surface functional groups.
[0054] In some embodiments, the oxygen anion is NO3 - PO4 3- 、SO4 2- .
[0055] In a specific embodiment, the hard carbon material satisfies the following formula 1 and / or formula 2:
[0056] 27%≤V cp / V p ×100%≤36% Formula 1,
[0057] 0.1%≤F≤0.5% Formula 2,
[0058] Among them, V cp is the closed pore volume of the hard carbon material, in cm 3 / g,V p is the pore volume of the hard carbon material, in cm 3 / g, F is the ash content of the hard carbon material.
[0059] In the implementation mode described above, by limiting the proportion of closed pores, the reversible sodium storage capacity of the closed-pore structure of the hard carbon material can be guaranteed, and irreversible dead sodium caused by excessive generation of closed pores can be avoided, thereby ensuring the reversible specific capacity of the battery.
[0060] In a specific embodiment, the hard carbon material satisfies the following formula 3 and formula 4:
[0061] V cp ×d 002 ×10 -7 =a Formula 3,
[0062] 0.5×10 -8 cm 4 / g≤a≤0.2×10 -7 cm 4 / g Formula 4,
[0063] Among them, V cp is the closed pore volume of the hard carbon material, in cm 3 / g,d 002 is the carbon interlayer spacing of hard carbon materials, in nm.
[0064] In the implementation method as described above, maintaining an appropriate proportion of closed-pore structure is correlated with the carbon interlayer spacing of the hard carbon material. On the one hand, it ensures the reversible sodium storage capacity of the hard carbon closed-pore structure and prevents excessive production of closed pores to cause irreversible dead sodium. On the other hand, it ensures a suitable carbon interlayer spacing to avoid the difficulty of sodium ions being inserted and removed due to excessive graphitization of small interlayer spacing.
[0065] In some embodiments, the specific surface area and pore volume of the hard carbon material can be directly measured by a specific surface area-pore size analyzer (BET-A 3H-2000BET-A); the closed pore volume of the hard carbon material is measured by small angle X-ray scattering SAXS analysis, and the interlayer spacing of the hard carbon material is measured by X-ray diffractometer XRD spectrum analysis. 002 get.
[0066] In one embodiment, 0.375 nm ≤ d 002 ≤0.395nm.
[0067] In some embodiments, the carbon inner core has a greater degree of graphitization than the hard carbon material.
[0068] In the implementation manner described above, since the degree of graphitization of the carbon inner core is greater than that of the hard carbon material, it can be concluded that the degree of graphitization of the carbon inner core is greater than that of the carbon shell of the carbon shell. In this way, on the one hand, good electronic conductivity and more interlayer spacing and lithium / sodium storage sites can be provided, which helps to improve the embedding and deintercalation efficiency of lithium / sodium ions, thereby improving the overall capacity and reversible specific capacity; on the other hand, the carbon inner core with a high degree of graphitization helps to form a more stable solid electrolyte interface (SEI) film during the first charging process, reduce the irreversible capacity loss, and improve the first efficiency; while the carbon shell has a lower degree of graphitization, on the one hand, it can provide additional lithium / sodium ion storage sites for the overall hard carbon material, further improving the reversible specific capacity of the hard carbon material, and on the other hand, it can alleviate the volume change during the charge and discharge process, maintain the integrity of the electrode structure, thereby further improving the battery's first efficiency and reversible capacity.
[0069] In a specific embodiment, the hard carbon material satisfies: the lattice constant (La) of the a-axis of the graphite crystal is 2-6 nm, and the lattice constant (Lc) of the c-axis of the graphite crystal is 1-1.5 nm;
[0070] The carbon core satisfies: the lattice constant (La) of the a-axis of the graphite crystal is 3-8nm, and the lattice constant (Lc) of the c-axis of the graphite crystal is 1.5-2nm.
[0071] The lattice constant of the a-axis of the graphite crystal represents the lateral size of the graphite crystal in the hard carbon material, that is, the size parallel to the graphite layer, which reflects the degree of order of the carbon atoms in the graphite layer; the lattice constant of the c-axis of the graphite crystal represents the vertical size of the graphite crystal in the hard carbon material, that is, the size perpendicular to the graphite layer, which reflects the degree of order of the graphite layer stacking. By limiting the lattice constant of the a-axis and the c-axis of the graphite crystal of the material, the degree of graphitization of the material can be reflected.
[0072] Among them, the lattice constant of the a-axis and the lattice constant of the c-axis of the hard carbon material can be directly obtained from the XRD refinement image of the hard carbon material, while the lattice constant of the a-axis and the lattice constant of the c-axis of the carbon core need to be calculated after the carbon shell of the hard carbon material is etched away and then the XRD refinement image is obtained.
[0073] In a second aspect, the present invention provides a method for preparing the positive electrode active material as described in the first aspect, comprising the following steps:
[0074] The carbon source and the heteroatom doping source are mixed and carbonized at 150-600° C. in a protective atmosphere for 0.5-6 h to obtain a precursor I;
[0075] The precursor I is subjected to secondary carbonization treatment at 900-1600° C. in a protective atmosphere for 1-10 hours to obtain the precursor II;
[0076] After the precursor II and the coating agent are mixed, the temperature is raised to 300-600°C at a heating rate of 1-5°C / min in a protective atmosphere, and the temperature is kept for 2-12 hours. The temperature is then raised to 800-1300°C at a heating rate of 1-10°C / min, and the temperature is kept for 1-10 hours to obtain the hard carbon material.
[0077] In the above preparation method, the carbon source and the heteroatom doping source are subjected to a low-temperature carbonization and a high-temperature carbonization to form a carbon core, at which the oxygen anions are evenly distributed in the core. After adding the coating agent, a carbon shell is formed by two-stage heat treatment. During the first heat preservation, while the carbon shell is formed, vacancies and pores are formed at the interface through the bonding effect between the oxygen anions on the surface of the carbon core and the carbon atoms in the shell. After the second heat preservation, the oxygen anions move and their concentration decreases from the core to the shell. In addition, the specific surface area of the hard carbon can be controlled within 5m 2 / g-15m 2 / g range.
[0078] Biomass raw materials have a wide range of sources, but poor consistency, and the stability of producing hard carbon materials is low. The above-mentioned preparation method is particularly suitable for biomass raw materials and can enhance the consistency of hard carbon materials prepared from different biomass raw materials. In a specific embodiment, the carbon source is lignin and / or cellulose materials; for example, the lignin raw material is selected from at least one of walnut shells, coconut shells, macadamia shells, poplar, pine, mahogany, etc., and the cellulose material is selected from plant branches and leaves, cotton and linen, etc.
[0079] In some embodiments, the carbon source is mixed after being pretreated; the pretreatment includes the following process:
[0080] The lignin and / or cellulose materials are pre-carbonized at 300-800° C. in a protective atmosphere, and the solid product obtained by the pre-carbonization is acid-washed to obtain the pre-treated carbon source.
[0081] Among them, the lignin and / or cellulose materials are pretreated as described above to control the degree of carbonization to obtain a carbon source with a certain impurity content (ash content), which can further reduce the product differences and instability caused by the differences in biomass raw materials.
[0082] In some embodiments, after the pre-carbonization treatment, a crushing treatment is also included. The particle size of the crushed particles is 10-20 mesh. After crushing, a carbon source with a certain pore size distribution can be obtained, which can further reduce the product differences and instability caused by the differences in biomass raw materials.
[0083] In some embodiments, the pickling temperature is 50-120° C., and the pickling agent used is one or more of sulfuric acid, hydrochloric acid, nitric acid, and hydrofluoric acid.
[0084] In a specific embodiment, the mass ratio of the heteroatom doping source to the carbon source is 1-5wt%.
[0085] The proportion of heteroatom doping sources affects the oxygen anions doped in the core, and the oxygen anions doped in the core affect the concentration change of oxygen anions and the carbon structure of the carbon shell. The implementation method described above can improve the conductivity and sodium ion storage performance of the hard carbon material by controlling the addition amount of the heteroatom doping source to further ensure the integrity of the carbon network of the hard carbon material.
[0086] In a specific embodiment, the heteroatom doping source includes at least one of urea, ammonium persulfate, melamine, ammonium polyphosphate, and sodium dodecyl sulfate.
[0087] Different types of coating agents result in different interfaces between the transition layer and the outer shell layer, and also different controls on the pore structure. Therefore, in order to achieve controllable adjustment of the material structure and properties and to bring out the optimal performance of the material, in a specific embodiment, the coating agent includes at least one of asphalt, phenolic resin, β-resin, glucose, and citric acid.
[0088] In some embodiments, the protective atmosphere involved in the above preparation method can be selected from nitrogen atmosphere and / or argon atmosphere.
[0089] In a third aspect, the present invention provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer coated on at least one surface of the current collector, wherein the negative electrode active material layer comprises the hard carbon material described in the first aspect.
[0090] Illustratively, the negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder and optionally a dispersant; wherein the negative electrode active material includes the above-mentioned hard carbon material; the conductive agent can be selected from at least one of carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the dispersant can be selected from at least one of sodium carboxymethyl cellulose, triethylhexyl phosphoric acid, and sodium dodecyl sulfate.
[0091] In a fourth aspect, the present invention provides a battery, comprising a positive electrode sheet and the negative electrode sheet described in the third aspect.
[0092] In some embodiments, the battery is a sodium ion battery.
[0093] The battery further includes a diaphragm; the present invention has no particular limitation on the diaphragm, and any known porous diaphragm with electrochemical stability and chemical stability can be selected, for example, at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The diaphragm can be single-layer or multi-layer.
[0094] The battery also includes an electrolyte, which includes an organic solvent and an electrolyte salt. The organic solvent is used as a medium for transmitting ions in the electrochemical reaction, and any organic solvent known in the art for battery electrolyte can be used.
[0095] Exemplarily, the organic solvent may be at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE). In a specific embodiment, two or more of the above organic solvents may be selected.
[0096] The electrolyte salt is used as a source of ions, and any electrolyte salt known in the art for battery electrolyte can be used. For example, the electrolyte salt can be at least one of sodium hexafluorophosphate, sodium fluorosulfonyl imide, sodium bis(trifluoromethylsulfonyl)imide, sodium tetrafluoroborate, and sodium perchlorate.
[0097] The battery of the present invention can be manufactured according to conventional methods in the art, such as stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, assembling the battery cell through a winding process or a stacking process, and then packaging and baking, injecting the electrolyte, and then hot pressing and other processes to obtain the battery.
[0098] The technical scheme of the present invention is further illustrated below in conjunction with specific examples. All parts, percentages and ratios described in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0099] Example 1
[0100] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, the doping amount of the oxygen anions is 3wt%, the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell, and the specific surface area of the hard carbon material is B=7.58m 2 / g; closed pore volume V of hard carbon materials cp =0.20cm 3 / g, the pore volume V of hard carbon materials p =0.63cm 3 / g, the specific surface area of hard carbon material V = 7.58 cm 3 / g, carbon interlayer spacing d of hard carbon materials 002 =0.384nm. Figure 2 This is the Raman image of the hard carbon material in this example. It can be seen from the figure that the I D / I G =0.87; Figure 3 This is the SEM image of the hard carbon material in this example.
[0101] The hard carbon material was etched to different depths using an IG2 ion source argon gun, and the materials at different etching depths were characterized by X-ray photoelectron spectroscopy (XPS). According to XPS testing, the P and N concentrations at the carbon shell were 0; in the direction from the carbon shell to the center of the carbon core, the P concentration at the etching depth of 15nm was 1.2wt%, and the N concentration was 0.5wt%; the P concentration at the etching depth of 50nm was 2.4wt%, and the N concentration was 1.1wt%.
[0102] The preparation method thereof comprises the following steps:
[0103] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0104] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0105] Step 3, high temperature carbonization, the precursor I of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0106] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1000°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain wood-based hard carbon materials.
[0107] Example 2
[0108] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0109] The preparation method thereof comprises the following steps:
[0110] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0111] Step 2, doping treatment, adding ammonium persulfate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0112] Step 3, high temperature carbonization, the precursor II of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0113] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1000°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain wood-based hard carbon materials.
[0114] Example 3
[0115] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0116] The preparation method thereof comprises the following steps:
[0117] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0118] Step 2, doping treatment, adding urea as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0119] Step 3, high temperature carbonization, the precursor I of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0120] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1000°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain wood-based hard carbon materials.
[0121] Example 4
[0122] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0123] The preparation method thereof comprises the following steps:
[0124] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0125] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 5wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0126] Step 3, high temperature carbonization, the precursor I of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0127] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1000°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain wood-based hard carbon materials.
[0128] Example 5
[0129] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0130] The preparation method thereof comprises the following steps:
[0131] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0132] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0133] Step 3, high temperature carbonization, the precursor I of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0134] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with glucose, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1000°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain wood-based hard carbon materials.
[0135] Example 6
[0136] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0137] The preparation method thereof comprises the following steps:
[0138] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0139] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0140] Step 3, high temperature carbonization, the precursor I of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0141] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with glucose, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1200°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain wood-based hard carbon materials.
[0142] Example 7
[0143] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0144] The preparation method thereof comprises the following steps:
[0145] Step 1, pre-carbonization-pure washing treatment, the poplar wood raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0146] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0147] Step 3, high temperature carbonization, the precursor I of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0148] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1000°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain wood-based hard carbon materials.
[0149] Example 8
[0150] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0151] The preparation method thereof comprises the following steps:
[0152] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 300°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0153] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0154] Step 3, high temperature carbonization, the precursor II of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 900°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0155] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1000°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain wood-based hard carbon materials.
[0156] Example 9
[0157] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0158] The preparation method thereof comprises the following steps:
[0159] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 800°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0160] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 150°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0161] Step 3, high temperature carbonization, the precursor II of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0162] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1000°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain wood-based hard carbon materials.
[0163] Example 10
[0164] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0165] The hard carbon material was etched to different depths using an IG2 ion source argon gun, and the materials at different etching depths were characterized by X-ray photoelectron spectroscopy (XPS). According to XPS testing, the concentrations of P and N in the unetched state were 0; in the direction from the carbon shell to the center of the carbon core, the P concentration at an etching depth of 15nm was 0.9wt%, and the N concentration was 0.3wt%; the P concentration at an etching depth of 50nm was 1.6wt%, and the N concentration was 0.7wt%.
[0166] The preparation method thereof comprises the following steps:
[0167] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0168] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 600°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0169] Step 3, high temperature carbonization, the precursor II of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0170] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1300°C at a heating rate of 2°C / min, treated for 4 hours, cooled to below 50°C and sampled, and finally obtained a wood-based hard carbon material after crushing and sieving.
[0171] Embodiment 11
[0172] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0173] The hard carbon material was etched to different depths using an IG2 ion source argon gun, and the materials at different etching depths were characterized by X-ray photoelectron spectroscopy (XPS). According to XPS testing, the concentrations of P and N in the unetched state were 0; in the direction from the carbon shell to the center of the carbon core, the P concentration at an etching depth of 15nm was 1.1wt%, and the N concentration was 0.4wt%; the P concentration at an etching depth of 50nm was 2.5wt%, and the N concentration was 1.2wt%.
[0174] The preparation method thereof comprises the following steps:
[0175] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0176] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0177] Step 3, high temperature carbonization, the precursor II of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 900°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0178] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 800°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain wood-based hard carbon materials.
[0179] Comparative Example 1
[0180] This example provides a hard carbon material, and a preparation method thereof comprises the following steps:
[0181] Step 1, pre-carbonization, the walnut shell raw material is heated to 600°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, the treatment time is 10 hours, the temperature is cooled to below 50°C, and then crushed to 10 meshes and sieved to obtain a precursor I;
[0182] Step 2, high temperature carbonization, the precursor I of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor II;
[0183] Step 3: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 1000°C at a heating rate of 2°C / min in a high-temperature furnace under a nitrogen atmosphere, and the treatment time is 4h. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain a wood-based hard carbon material.
[0184] Comparative Example 2
[0185] This example provides a hard carbon material, and a preparation method thereof comprises the following steps:
[0186] Step 1: Pre-carbonization-pure washing treatment, the walnut shell raw material was pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and then pure washed with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0187] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0188] Step 3, high temperature carbonization, the precursor II of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain a hard carbon material.
[0189] The hard carbon material was etched to different depths using an IG2 ion source argon gun, and the materials with different etching depths were characterized by X-ray photoelectron spectroscopy (XPS). XPS testing showed that the P concentration of the unetched, etched depth of 15nm and etched depth of 50nm was 1.9wt%, and the N concentration was 0.9wt%.
[0190] Figure 6 This is the Raman image of the hard carbon material. It can be seen from the figure that the I D / I G =0.818.
[0191] Comparative Example 3
[0192] This example provides a hard carbon material, which includes a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, wherein the carbon core is doped with oxygen anions, wherein the oxygen anions contain P and N heteroatoms, and the concentration of the heteroatoms is consistent from the center of the carbon core to the direction close to the carbon shell. For other structural parameters, see Table 1.
[0193] The IG2 ion source argon gun etches the hard carbon material at different depths, and the materials at different etching depths are characterized by X-ray photoelectron spectroscopy (XPS). According to XPS testing, the P concentration of the unetched carbon is 0wt%; in the direction from the carbon shell to the center of the carbon core, the P concentration at the etching depths of 10 and 50nm is both 2.1wt%, and the N concentration is both 0.9wt%.
[0194] The preparation method thereof comprises the following steps:
[0195] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0196] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 3wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0197] Step 3, high temperature carbonization, the precursor I of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0198] Step 4: Coating process, the precursor II of step 2 is crushed and mixed with phenolic resin, heated to 1000°C at a heating rate of 2°C / min in a high-temperature furnace under a nitrogen atmosphere, and the treatment time is 4h. After cooling to below 50°C, samples are taken, and the wood-based hard carbon material is finally obtained after crushing and screening.
[0199] Comparative Example 4
[0200] This example provides a hard carbon material, and a preparation method thereof comprises the following steps:
[0201] Step 1, pre-carbonization-pure washing treatment, the walnut shell raw material is pre-carbonized at 600°C for 10 hours, crushed to 10 mesh, sieved, and subjected to pure washing treatment with 1M sulfuric acid + 1M hydrochloric acid at 80°C, and then dried and sampled to obtain precursor I;
[0202] Step 2, doping treatment, adding ammonium polyphosphate as a heteroatom doping source to the precursor I of step 1, with a doping ratio of 10wt%, heating to 500°C at a heating rate of 2°C / min in a medium temperature furnace under a nitrogen atmosphere, treating for 6h, cooling to below 50°C and sampling to obtain precursor II;
[0203] Step 3, high temperature carbonization, the precursor I of step 1 is subjected to high temperature carbonization in a high temperature furnace, the temperature is increased to 1400°C at a heating rate of 3°C / min under a nitrogen atmosphere, the treatment time is 2h, and the temperature is cooled to below 50°C and then sampled to obtain the precursor III;
[0204] Step 4: The precursor II of step 2 is crushed and mixed with the phenolic resin, heated to 500°C at a heating rate of 1°C / min in a high-temperature furnace under a nitrogen atmosphere and kept warm for 2 hours, then heated to 1000°C at a heating rate of 2°C / min, and the treatment time is 4 hours. After cooling to below 50°C, samples are taken, and crushed and sieved to finally obtain a wood-based hard carbon material.
[0205] Application Example 1
[0206] This example provides a series of negative electrode sheets, and the preparation method thereof includes the following steps:
[0207] The hard carbon materials of each embodiment and comparative example were mixed with conductive carbon black (SP) and sodium carboxymethyl cellulose in a mass ratio of 95g:2g:3g, 200mL of water was added, and the mixture was stirred for 1h to obtain a mixed slurry. The mixed slurry was coated on a copper foil to a coating thickness of 100μm. The mixture was vacuum dried at 100°C for 6h to obtain a series of negative electrode sheets.
[0208] Application Example 2
[0209] This example provides a series of sodium ion batteries, the preparation method of which includes the following steps:
[0210] The electrode sheet prepared in Application Example 1 was used as the positive electrode, sodium as the negative electrode, 1 mol / L NaPF6 was dissolved in ethylene carbonate (EC): dimethyl carbonate (DMC): propylene carbonate (PC) = 1:1:1, and 1 wt% of fluoroethylene carbonate (FEC) was used as the electrolyte additive, and the separator was glass fiber (GF / A). The battery was assembled in an argon-filled glove box and aged for 24 hours before charge and discharge tests were performed.
[0211] Characterization and testing
[0212] 1. Use BET analyzer to test the specific surface area and pore volume of each hard carbon material;
[0213] 2. Use X-ray diffractometer to test the interlayer spacing d002, La and Lc of each hard carbon material;
[0214] 3. Use ICP to test the P content of the hard carbon material, use an element analyzer to test the S and N content of the hard carbon material, and then calculate the doping amount of oxygen anions;
[0215] 4. Use an X-ray small angle diffractometer to test the closed pore volume of each hard carbon material; use an ash content tester to test the ash content of each hard carbon material;
[0216] 5. The first week charge and discharge specific capacity and the first coulomb efficiency (first efficiency) of each battery were obtained by testing with a battery test cabinet. The first coulomb efficiency (%) = first charge specific capacity / first discharge specific capacity × 100. The results are shown in Table 2.
[0217] The structural characteristics of the hard carbon materials of the above examples and comparative examples are summarized in Table 1.
[0218] Table 1
[0219]
[0220]
[0221] Table 2:
[0222]
[0223]
[0224] It can be seen from Table 2 that the battery prepared from the hard carbon material of the embodiment has a higher reversible specific capacity and first efficiency than the comparative example. In detail, the measured reversible specific capacity of the hard carbon material of the comparative example is difficult to exceed 290 mAh / g, the first efficiency is low, and there are problems such as low capacity, low first efficiency, difficulty in improving, and substandard physical and chemical indicators. The hard carbon material of the embodiment is modified through multiple steps (doping modification-high temperature carbonization-coating modification), which effectively improves the sodium storage capacity and first efficiency of the hard carbon material.
[0225] Further, from Figure 3 and 7 It can be seen that the hard carbon material particles of comparative example 2 have more pore structures on the surface, and the hard carbon material particles of embodiment 1 have a smooth surface and no obvious holes on the surface. Combined with the results in Table 2, it can be seen that the coating has a great difference in the structure of the hard carbon material, which in turn affects the overall sodium storage capacity and initial efficiency of the material. Figure 2 , 6 and Figure 4 , 8 It can be seen from the Raman spectrum and XRD spectrum that the graphitization degree of the hard carbon material in Example 1 is lower. Figure 5 , 9 From the charge and discharge curves, it can be seen that the hard carbon material used for the battery has a higher platform capacity and reversible specific capacity.
[0226] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A hard carbon material, characterized in that: The hard carbon material comprises a carbon core and a carbon shell located on at least a portion of the surface of the carbon core, the carbon core is doped with oxygen anions, the oxygen anions contain heteroatoms, and the concentration of the heteroatoms decreases from the center of the carbon core to the direction close to the carbon shell, and the specific surface area of the hard carbon material is B, and B satisfies 5m 2 / g≤B≤15m 2 / g.
2. The hard carbon material according to claim 1, characterized in that In the hard carbon material, the doping amount of oxygen anions is 1-5wt%; Preferably, the heteroatom includes at least one of N, P and S.
3. The hard carbon material according to claim 1, characterized in that The hard carbon material satisfies the following formula 1 and / or formula 2: 27%≤V cp / V p ×100%≤36% Formula 1, 0.1%≤F≤0.5% Formula 2, Among them, V cp is the closed pore volume of the hard carbon material, in cm 3 / g,V p is the pore volume of the hard carbon material, in cm 3 / g, F is the ash content of the hard carbon material.
4. The hard carbon material according to any one of claims 1 to 3, characterized in that: The hard carbon material satisfies the following formula 3 and formula 4: V cp ×d 002 ×10 -7 =a Formula 3, 0.5×10 -8 cm 4 / g≤a≤0.2×10 -7 cm 4 / g Formula 4, Among them, V cp is the closed pore volume of the hard carbon material, in cm 3 / g,d 002 is the carbon interlayer spacing of hard carbon materials, in nm.
5. The hard carbon material according to claim 4, characterized in that <h2 style=";text-align:left;direction:ltr">0.375nm≤d<h2 style=";text-align:left;direction:ltr"> 002 <h2 style=";text-align:left;direction:ltr"> ≤0.395nm.
6. The hard carbon material according to any one of claims 1 to 5, characterized in that: The degree of graphitization of the carbon core is greater than the degree of graphitization of the hard carbon material; Preferably, the hard carbon material satisfies: the lattice constant of the a-axis of the graphite crystal is 2-6 nm, and the lattice constant of the c-axis of the graphite crystal is 1-1.5 nm; The carbon core satisfies: the lattice constant of the a-axis of the graphite crystal is 3-8nm, and the lattice constant of the c-axis of the graphite crystal is 1.5-2nm.
7. A method for preparing the hard carbon material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The carbon source and the heteroatom doping source are mixed and carbonized at 150-600° C. in a protective atmosphere for 0.5-6 h to obtain a precursor I; The precursor I is subjected to secondary carbonization treatment at 900-1600° C. in a protective atmosphere for 1-10 hours to obtain the precursor II; After the precursor II and the coating agent are mixed, the temperature is raised to 300-600°C at a heating rate of 1-5°C / min in a protective atmosphere, and the temperature is kept for 2-12 hours. The temperature is then raised to 800-1300°C at a heating rate of 1-10°C / min, and the temperature is kept for 1-10 hours to obtain the hard carbon material.
8. The preparation method according to claim 7, characterized in that: The carbon source is lignin material and / or cellulose material; Preferably, the carbon source is mixed after being pretreated; the pretreatment includes the following process: The lignin and / or cellulose materials are pre-carbonized at 300-800° C. in a protective atmosphere, and the solid product obtained by the pre-carbonization is acid-washed to obtain the pre-treated carbon source.
9. The preparation method according to claim 7, characterized in that: The mass ratio of the heteroatom doping source to the carbon source is 1-5wt%; Preferably, the heteroatom doping source includes at least one of urea, ammonium persulfate, melamine, ammonium polyphosphate, and sodium dodecyl sulfate; Preferably, the coating agent includes at least one of asphalt, phenolic resin, beta resin, glucose and citric acid.
10. A negative electrode sheet, comprising a current collector and a negative electrode active material layer coated on at least one surface of the current collector, characterized in that: The negative electrode active material layer comprises the hard carbon material described in any one of claims 1 to 6 or the hard carbon material prepared by the preparation method described in any one of claims 7 to 9.
11. A battery comprising a positive electrode sheet and the negative electrode sheet according to claim 10.
Citation Information
Cited By
Negative electrode hard carbon material, preparation method thereof, negative electrode composition, sodium ion secondary battery and application
CN120978067A
Reconstruction method and application of C= O functional group on surface of coconut shell-based hard carbon material
CN121591211A